Islamophobia and Allegations Against Corona Virus Spread By Muslim Minority In India - Muhammad Saekul Mujahidin (AJIS: Academic Journal of Islamic Studies, 2021)
This article discusses Islamophobia and accusations by the Hindu majority against Muslim minorities in India against the coronavirus. The Bharatiya Janata Party (BJP) is one of the parties that often voices accusations against Muslim minorities in India for this incident. The Tablighi Jamaat in New Delhi is one of the targets and accusations of the Hindu majority against Muslims in India. The purpose of this study is to find out the reasons why Hindus accuse Muslims in India of being the cause of the spread of the coronavirus "Covid-19". This paper uses a qualitative descriptive method with secondary data collection. The data were obtained from literature studies including books, journals, or those related to research. The findings of this study show that Hindus hate Islam for a long time, coupled with the activities of the Tablighi Jamaat which make them hate Muslims even more and accuse them of being the spreaders of the Covid-19 coronavirus. Not only that, the majority of Hindus create hashtags on social media, such as #CoronaJihad, #BioJihad or #MuslimMeaningTerrorist, all of which are used to increase hatred and rally the Hindus community against Muslims in India during the pandemic.